Heat and superdiffusive melting fronts in unsaturated porous media - Flekkøy, Eirik G.; Hansen, Alex; Eiser, Erika (Frontiers in Physics, 2025)
When water is present in a medium with pore sizes in a range of approximately 10 nm, the corresponding freezing-point depression will cause long-range broadening of a melting front. Describing the freezing-point depression by the Gibbs–Thomson equation and the pore-size distribution by a power law, we derive a nonlinear diffusion equation for the fraction of melted water. This equation yields superdiffusive spreading of the melting front with a diffusion exponent, which is given by the spatial dimension and the exponent describing the pore size distribution. We derive this solution analytically from energy conservation in the limit where all the energy is consumed by the melting and explore the validity of this approximation numerically. Finally, we explore a geological application of the theory to the case of one-dimensional subsurface melting fronts in granular or soil systems. These fronts, which are produced by heating of the surface, spread at a superdiffusive rate and affect the subsurface to significantly larger depths than a system without the effects of freezing-point depression.